A Modeling Study of Seasonal and Inter-annual Variations of the Arctic Black Carbon and Sulphate Aerosols - Huang, Li
The modeling results of current global aerosol models agree, generally within a factor of two, with the measured surface concentrations of black carbon (BC) and sulphate (SF) aerosols in rural areas across the northern continents. However, few models are able to capture the observed seasonal cycle of the Arctic aerosols. In general, the observed seasonality of the Arctic aerosols is determined by complex processes, including transport, emissions and removal processes. In this work, the representations of aerosol deposition processes (i.e., dry deposition, in-cloud and below-cloud scavenging) within the framework of the Canadian Global Air Quality Model – GEM-AQ are first enhanced. Through the enhancements in GEM-AQ, the seasonality of the Arctic BC and SF is reproduced, and the improvement in model performance extends to the rest of the globe as well. Then, the importance of these deposition processes in governing the Arctic BC and SF seasonality is investigated. It is found that the observed seasonality of the Arctic BC and SF is mainly caused by the seasonal changes in aerosol wet scavenging, as well as the seasonal injection of aerosols from surrounding source regions. Being able to reproduce the seasonality of the Arctic BC, the enhanced GEM-AQ allows more accurate assessment of the contributions of anthropogenic sources to the BC abundance in the Arctic air and deposition to the Arctic surface. Simulating results on regional contributions to the Arctic BC show a strong dependence on altitude. The results reinforce the previous finding of Eurasia being the dominant contributor to the surface BC in the Arctic, and suggest a significant contribution from Asian Russia. In addition to the seasonality of the Arctic aerosols, the inter-annual variation in the Arctic BC surface concentration is also investigated. To complement the 3-D GEM-AQ model, the atmospheric backward trajectory analysis, together with estimated BC emissions, is implemented as a computational effective approach to reconstruct BC surface concentrations observed at the Canadian high Arctic station, Alert. Strong correlations are found between the reconstructed and the measured BC in the cold season at Alert between 1990 and 2005, which implies that atmospheric transport and emissions are the major contributors to the observed inter-annual variations and trends in BC. The regional contributions estimated annually from 1990 through 2005 suggest that Eurasia is the major contributor in winter and spring to the near-surface BC level at Alert with a 16-year average contribution of over 85% (specifically 94% in winter and 70% in spring). A decreasing trend in the Eurasian contribution to the Arctic is found in this study, which is mainly due to regional emission reduction. However, the inter-annual variation in the North American contribution shows no clear trend. PhD